GIS-material for the archaeological project: A road in Hackefors - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to local plan work within the property Hackefors 5:1 in Landeryd parish, Linköping municipality, an archaeological survey (stage 2) was performed. In area 1-3 no archaeological remains were found. In area 4, remains of a road and a possible farmyard were discovered. The road ought to be constructed before 1692 since it is marked on a map from this year. No further archaeological measures are suggested to be taken within areas 1-3. A preliminary survey is suggested for area 4.

Purpose:

The information in the abstract is translated from the archaeological report:
The purpose of the survey was to determine if the area contained any unmarked archaeological remains.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Ett område inom Hackefors 5:1 är föremål för detaljplaneläggning i Landeryds socken, Linköpings kommun. Under den arkeologiska utredningen, etapp 2, påträffades inom område 1-3 inga fornlämningar medan det inom område 4 påträffades rester efter en väg och en stenpackning som eventuellt utgjort en gårdsplan. Vägen bör vara anlagd innan 1692 då den är markerad på en karta från detta år. Inom område 1-3 föreslås ingen vidare åtgärd medan det föreslås en förundersökning för område 4.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den arkeologiska utredningen, etapp 2, var att undersöka om det fanns fornlämningar som inte var synliga ovan mark inom de aktuella ytorna.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: En väg i Hackefors
Keywords: historical period; historisk tid; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi